Elementary School Teacher Problems in Facing the Independent Curriculum as Seen from Driving Schools - Ni Made Wedhani Yulia Putri; Putu Nanci Riastini (Universitas Pendidikan Ganesha, 2023)
An independent curriculum is a curriculum that is developed as a more flexible curriculum, focuses on essential material, and is one of the curriculum concepts that demands student independence. The implementation of the independent curriculum is, of course, related to teachers at school; the role of teachers is very much needed in implementing the independent curriculum when learning takes place. This research aims to analyze the problems experienced by elementary school teachers in dealing with the independent curriculum in driving schools. The type of research carried out is descriptive research. The research subjects were class I and IV teachers at the driving school, totalling 26 teachers. Data collection used the Likert scale questionnaire method. Data analysis uses percentages. The findings of this research show that 3 aspects could be improved for driving school teachers in facing the independent curriculum, namely developing overall learning outcomes, learning through projects, and developing student character. Factors that cause problems for school teachers driving curriculum changes are teachers' need for more understanding of the curriculum, lack of socialization process for the new curriculum, lack of teacher awareness, and low teacher motivation. This research can overcome the problems of teachers in dealing with the independent curriculum for elementary school students to improve education implementation throughout Indonesia.